EV71 infection induces neurodegeneration via activating TLR7 signaling and IL-6 production - Luo, Zhen; Su, Rui; Wang, Wenbiao; Liang, Yicong; Zeng, Xiaofeng; Shereen, Muhammad Adnan; Bashir, Nadia; Zhang, Qi; Zhao, Ling; Wu, Kailang; Liu, Yingle; Wu, Jianguo (PLoS pathogens, 2019)
As a neurotropic virus, human Enterovirus 71 (EV71) infection causes hand-foot-and-mouth disease (HFMD) and may develop severe neurological disorders in infants. Toll-like receptor 7 (TLR7) acts as an innate immune receptor and is also a death receptor in the central nervous system (CNS). However, the mechanisms underlying the regulation of TLR7-mediated brain pathogenesis upon EV71 infection remain largely elusive. Here we reveal a novel mechanism by which EV71 infects astrocytes in the brain and induces neural pathogenesis via TLR7 and interleukin-6 (IL-6) in C57BL/6 mice and in human astroglioma U251 cells. Upon EV71 infection, wild-type (WT) mice displayed more significant body weight loss, higher clinical scores, and lower survival rates as compared with TLR7-/- mice. In the cerebral cortex of EV71-infected mice, neurofilament integrity was disrupted, and inflammatory cell infiltration and neurodegeneration were induced in WT mice, whereas these were largely absent in TLR7-/- mice. Similarly, IL-6 production, Caspase-3 cleavage, and cell apoptosis were significantly higher in EV71-infected WT mice as compared with TLR7-/- mice. Moreover, EV71 preferentially infected and induced IL-6 in astrocytes of mice brain. In U251 cells, EV71-induced IL-6 production and cell apoptosis were suppressed by shRNA-mediated knockdown of TLR7 (shTLR7). Moreover, in the cerebral cortex of EV71-infected mice, the blockade of IL-6 with anti-IL-6 antibody (IL-6-Ab) restored the body weight loss, attenuated clinical scores, improved survival rates, reduced the disruption of neurofilament integrity, decreased cell apoptotic induction, and lowered levels of Caspase-3 cleavage. Similarly, in EV71-infected U251 cells, IL-6-Ab blocked EV71-induced IL-6 production and cell apoptosis in response to viral infection. Collectively, it's exhibited TLR7 upregulation, IL-6 induction and astrocytic cell apoptosis in EV71-infected human brain. Taken together, we propose that EV71 infects astrocytes of the cerebral cortex in mice and human and triggers TLR7 signaling and IL-6 release, subsequently inducing neural pathogenesis in the brain.